On expressionistic mysterium: Michael Chekhov's tragic character on page and on stage. Issue 2 (2nd July 2016) - Meerzon, Yana
Abstract: The 1924 Moscow Art Theatre II's production of Shakespeare's Hamlet, featuring Michael Chekhov in the leading part, became the artistic and conceptual touchstone for many Russians in understanding the inner dilemma of the protagonist. It revealed Chekhov's spiritual battles as a follower of Rudolf Steiner's anthroposophy, and as this article sets to argue, it became an example of modern mysterium (Fuchs, The Death of Character ), confirming in its themes and aesthetics to the style of expressionism emerging on European stages. In Chekhov's Hamlet, critics saw an "expressionistic tragedy, " a reading of Shakespeare's play that "represented a complete break with the traditional Russian interpretations of Hamlet as a spineless, superfluous man. Chekhov's Hamlet was restless; a man of action led to examination of the fundamental question of good and evil." (Law, "Chekhov's Russian Hamlet") This vision demanded new expressive means; so Hamlet also became the testing ground for Chekhov's own method of acting training, reflecting the subjectivity of the twentieth-century actor. In this article, I demonstrate that Chekhov`s work on Hamlet was his homage to the theatre of modern mysterium in the style of expressionism. First, I outline the stylistic parameters of the genre; then, I identify the formal elements that made up Russian theatrical expressionism, as seen in Eugeny Vakhtangov and Michael Chekhov's collaborative work. The third part is dedicated to the detailed analysis of the 1924 staging of Hamlet and concludes with my reading of Chekhov's work as an ultimate example of Fuch's theory.